A new scheme for automatic 2D detection of spheric and aspheric femoral heads: A case study on coronal MR images of bilateral hip joints of patients with Legg-Calve-Perthes disease - Memis, Abbas; Albayrak, Songul; Bilgili, Fuat (ELSEVIER IRELAND LTD, 2019)
Background and objective: In orthopaedics, hip joint and circular structure of the femoral head can be distorted by a wide variety of hip joint disorders. Hence, automatic detection and segmentation of the femoral head is an important issue in the studies of computerized hip joint segmentation, quantification and assessment. In the proposed study, we need to detect the center coordinates and radius of spheric and aspheric femoral heads automatically in bilateral hip magnetic resonance (MR) images using a new scheme. Methods: This paper presents a new two-level scheme based on the Circular Hough Transform (CHT) and Integro-differential Operator (IDO) to detect the spheric and aspheric femoral heads in MR images in 2D. Initially, MR slices are divided vertically into two equal halves to automatically separate the hip joints and Canny's edge detection method is performed on each of the halves to obtain edge images. Then, healthy and pathological femoral heads are detected by performing the CHT over edge images in the first stage of proposed scheme. In the second stage, femoral head circle detected with CHT is fine tuned by performing Daugman's IDO. Results: Performance evaluations of the proposed femoral head detection scheme were carried out on healthy and pathological hip joints in 24 coronal MR image sections belong to 13 patients with Legg-Calve-Perthes Disease (LCPD). In performance evaluations on 24 healthy and 24 pathological hip joints, Root Mean Square Error (RMSE) and Dice Similarity Coefficient (DSC) values were measured for automatically detected femoral heads. We observed 1.96 mm. (std. 1.21 mm.) mean RMSE for center coordinates, 1.45 mm. (std. 1.39 mm) mean RMSE for radii, 0.8978 (std. 0.0733) mean DSC on healthy femoral heads and 3.56 mm. (std. 3.19 mm.) mean RMSE for center coordinates, 1.56 mm. (std. 1.33 mm.) mean RMSE for radii, 0.8529 (std. 0.0927) mean DSC on pathological femoral heads. Conclusions: Proposed femoral head detection scheme has promising results for the detection and the segmentation of the spheric and aspheric femoral heads and also has a potential to be used in detection of the other anatomical structures having a circular shape. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Femoral head detection; MR image segmentation; Medical image analysis; Legg-Calve-Perthes disease; Circular hough transform; Integro-differential operator; SEGMENTATION; Computer Science; Engineering; Medical Informatics